Post Brexit and Post‐Covid: Reflections on the Contemporary Conservative Party. Issue 3 (12th June 2021) - Peele, Gillian
Abstract: This article analyses the changing character of the contemporary Conservative Party. It argues that the period since the Brexit referendum has seen the creation of a new politics in which voter alignments have shifted, and that the experience of the Covid pandemic has created a new agenda of issues facing government. Taken together, these developments constitute formidable challenges to the Conservative Party as it seeks to maintain its electoral support and its ability to manage the politics of power.